Blood Pressure Trends and Their Association with Cardiovascular Risk Factors in a Tertiary Care Population - FAISAL, AMNA; GHAFFAR, FATIMA; AHMED, HIRA; ASIF, KHADEEJA; VIRK, HANIF BATOOL (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Cardiovascular disease is a major global problem due to hypertension, and this is especially true in low and middle-income countries. This is important as it helps identify its association with modifiable risk factors so that early interventions and prevention are possible. Objective: In order to assess blood pressure trends and their relation with cardiovascular risk factors in a tertiary care population in Pakistan. Methods: This was a cross-sectional study conducted at the University of Lahore Teaching Hospital during July 2023 to July 2024. Sixty adult patients were enrolled. AHA 2017 guidelines were followed for categorization of blood pressure. Demographics, BMI, diabetes status, lipid profile, smoking, and family history of CVD were collected. SPSS v25 was used for statistical analysis, including multivariate logistic regression. Results: Hypertension was present in 60% of 60 subjects (mean age 51.3 ± 12.6 years). Hypertension was significantly associated with obesity (p=0.011), diabetes (p=0.042), smoking (p=0.045), and elevated LDL (p=0.004). Obesity (OR=2.74, p=0.024) and diabetes (OR=2.58, p=0.048) were found to be independent predictors by multivariate analysis. Conclusion: Obesity and diabetes are closely associated with the high burden of hypertension in this population. Reduction of long-term morbidity is dependent on early identification and integrated cardiovascular risk management. The tertiary care and community health settings should prioritize a preventive strategy based on lifestyle modification.